Financial Issues Impacting Health And Solutions - Vishwambhar V. Jadhav (Elementary Education Online, 2023)
The present paper is highlighting financial issues faced during unprecedented situations. Also, it presents on how mentally and physically fit individual can overcome such challenges. Even RBI has observed that in future India and other countries will face recession, and it will affect all over the world which will affect the financial strength of individual and society as well as their standard of living My paper will try to analyze the financial issues faced in critical conditions and effects of same on individual health during the every aspect in their life and further analyze the remedies to overcome such situation.